(untitled) (Bangladesh Journal of Medical Science, 2023)
Objective: The objective of this study was to investigate the knowledge, vaccine preference and fear of COVID-19 among Malaysians. Materials and Methods: This online questionnaire survey was carried out from 6th September 2021 to 12th November 2021 through Google form on adult Malaysians. To collect the data, a pilot-tested validated questionnaire was administered to 387 samples. The questionnaire comprised of participants’ socio-demographic characteristics, knowledge on COVID-19 vaccine with source of information, participants’ specific vaccine preferences with reasons, vaccination status and fear on COVID-19. Results and Discussions: Participants has good knowledge on COVID-19 vaccina. Total 275(71%) participants showed preference for specific vaccine; Pfizer-BioNTech was the most preferred (61.5%) vaccine. The major reason for preference was effectiveness (56.4%). Participants with vaccinepreferred group obtained higher knowledge-score(7.38/8) than non-preferred (7.28/8) with insignificant difference. A total of 376(97%) respondents were vaccinated, among them 250 (66.5%) received preferred vaccine and 22(5.85%) received non-preferred, while rest had no preference. Among 11 non-vaccinated participants, three denied vaccinations as they were offered non-preferred vaccines. Fear of COVID-19 score was found higher (21.34/35) in the vaccinated group compared to non-vaccinated group (19.09/35), although no significant difference was observed. Conclusion: Most of the Malaysians are knowledgeable about COVID-19 vaccination, have vaccine-preference and vaccinated. Vaccine-preferred participants are more knowledgeable than non-preferred with insignificant difference. Among the non-vaccinated participants, 27% (3/11) denied vaccination as offered non-preferred vaccine. Vaccinated group showed more fear of COVID-19 than non-vaccinated, with an insignificant difference. Increased awareness is necessary for the people, unwilling or hesitant to vaccinate. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 135-144